(untitled) (Sociologisk Forskning, 2017)
Resettlement, Swedenprogram, and the notion of the "passive refugee" This study analyzes discourses of refugees as manifested in a part of the Swedish resettlement work called the Swedenprogram. The aim of the programs is to, through dialogue; actively involve refugees in their resettlement. The program can be situated within an overall increased emphasis on activating refugees and asylum seekers in order for them to take responsibility for their integration. Video observations were carried out of nine Swedenprograms that were held in Kenya and Sudan. The information provided by the delegations is based on the notion of ideal citizen as active, responsible, and engaged in self-fulfillment. However, the study also shows that the information given to the youth positions them as potentially lacking these traits. The idea of the passive refugee permeates the information in different ways and includes a gender aspect. The study also shows how the youths navigate and sometimes resist the stereotype positioning of themselves.